AN INFORMATION SYSTEM OF INTEGRATED TRANSPORT SYSTEM (Perner's Contacts, 2011)
The paper deals with a problematic of information systems of integrated transport systems. It solves the basic assumptions and goals, basic components and the content, including information service for these information systems.
Keywords: integrated transport system; trip phases; information system; information service